Donor pretreatment with carbamylated erythropoietin in a brain death model reduces inflammation more effectively than erythropoietin while preserving renal function. - Nijboer, W; Ottens, P; van Dijk, A; van Goor, H; Ploeg, R; Leuvenink, H (2010)
OBJECTIVE: We hypothesized that donor treatment of deceased brain dead donors would lead to a decrease in inflammatory responses seen in brain death and lead to a restoration of kidney function. DESIGN: A standardized slow-induction rat brain death model followed by evaluation of kidney function in an isolated perfused kidney model. SETTINGS: Surgery Research Laboratory, University Medical Center Groningen, the Netherlands. SUBJECTS: Male Fisher rats. INTERVENTIONS: Donor treatment with erythropoietin, carbamylated erythropoietin, which lacks erythropoietic activity, or vehicle. MEASUREMENTS AND MAIN RESULTS: In brain death, carbamylated erythropoietin and, to a lesser extent, erythropoietin were able to decrease the expression of several proinflammatory genes and to decrease the infiltration of polymorphonuclear cells in the kidney. No effect on tubular injury parameters was seen. Kidney function decreased almost by 50% after brain death but was fully restored after treatment with both carbamylated erythropoietin and erythropoietin. CONCLUSIONS: Carbamylated erythropoietin can inhibit the inflammatory response caused by brain death more effectively than erythropoietin, whereas both substances can restore kidney function after brain death.